Peningkatan Mutu Pendidikan Luar Sekolah dalam Upaya Pembangunan Sumber Daya Manusia - I Ketut Sudarsana (UHN IGB Sugriwa Denpasar, 2015)
The major challenge for the Indonesian nation these days and in the coming is how to improve the quality of the people. Regarding that it is interesting to study the present quality of the education and to know what can be done to it so that it improves and produces better human resources that are productive, efficient, confident, and competetive in the global context.